2016
DOI: 10.1016/j.fuproc.2016.02.039
|View full text |Cite
|
Sign up to set email alerts
|

Effect of briquette composition and size on the quality of the resulting coke

Abstract: Five briquettes were prepared using sawdust, a non-coking coal and a binder.Industrial coal blends were used to study the influence of the type of sawdust (pine and chestnut), the binder (coal tar and coal-tar sludge) and the size of the briquettes on the quality of the cokes produced from mixtures containing up to 15 wt.% of the five briquettes. The effect of the briquettes and briquette components on the fluidity of the industrial coal blends was investigated. It was found that biomass and non-coking coal pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 31 publications
2
28
0
Order By: Relevance
“…The reactivity of the bio-cokes increases when the proportion of charcoal increases. This is in line with the previous research [33][34][35]. The higher reactivity of the bio-cokes is attributed to the ash composition of the raw materials, oxygen content, the inhibition of fluidity development in the carbonized blend, the presence of porous isotropic particles from the biomass, functionality of the biomass material, and the microporosity of the cokes [36].…”
Section: Impact Of Charcoal Particle Size On the Reactivitysupporting
confidence: 90%
“…The reactivity of the bio-cokes increases when the proportion of charcoal increases. This is in line with the previous research [33][34][35]. The higher reactivity of the bio-cokes is attributed to the ash composition of the raw materials, oxygen content, the inhibition of fluidity development in the carbonized blend, the presence of porous isotropic particles from the biomass, functionality of the biomass material, and the microporosity of the cokes [36].…”
Section: Impact Of Charcoal Particle Size On the Reactivitysupporting
confidence: 90%
“…25) It is considered that pitch dispersion lowered CRI in this case. This effect appears only in test 4 because CRI in test 4 (over 25) is higher than that in the other tests (15)(16)(17)(18)(19)(20)(21)(22) and CRI is easily to be lowered by pitch dispersion.…”
Section: Effect Of Briquette Size On the Mean Size Of Cokementioning
confidence: 93%
“…In the study of Montiano et al, 16) the weight of the briquette 23 g and 4-6 g corresponds to volume of 20.0-26.3 cm 3 and 4.4-5.7 cm 3 (based on apparent density of 1.149-0.873 g/cm 3 ) and to equivalent sphere volume diameter of 33.7-36.9 mm and 20.3-22.2 mm respectively. In the case of briquette blending ratio of 15%, DI 150 15 for smaller briquette is larger than that for larger briquette, which corresponds to test 1 of this study.…”
Section: -15mentioning
confidence: 99%
See 1 more Smart Citation
“…However, as discussed earlier, adding biomass to coal blend leave behind bio-coke with poor mechanical properties compared to conventional coke. Some studies showed that even adding 3% sawdust to the coal blend prior to coking has negatively affected the product mechanical properties [72,74] while other studies stated that up to 5% biomass can be added to the coking coal blend without significant deterioration of the produced coke properties [70,72,75].…”
mentioning
confidence: 99%